The Isle of The Dead Benchmark, the Sydney, Fort Denison Tide Gauge and the Ipcc Ar5 Chapter 13 Sea Levels Revisited - Parker, Albert (Quaestiones Geographicae, 2015)
The paper revisits the Isle of the Dead benchmark and the Sydney, Fort Denison tide gauge to confirm that long term, high quality tide gauges are acceleration free, consistently to the analysis of key sites suggesting the sea levels are not sharply raising following the carbon dioxide emissions. The paper also discusses the flaws of the IPCC AR5 Chapter13 Sea levels. The time history of the relative rate of rise computed by linear fitting of the data locally collected by tide gauges is the best parameter to assess the effect of global warming providing length and quality requirements are satisfied. There is no reason to search for less reliable alternative methods because the climate models predicted different trends. The Global Positioning System (GPS) inferred vertical tide gauge velocity suffers of significant inaccuracies. Larger inaccuracies are provided by the satellite altimetry Global Mean Sea Level (GMSL) that is a computation and not a measurement.